2020
DOI: 10.3389/feart.2020.601415
|View full text |Cite
|
Sign up to set email alerts
|

Post-Depositional Fluid Flow in Jurassic Sandstones of the Uncompahgre Uplift: Insights From Magnetic Fabrics

Abstract: The anisotropy of magnetic susceptibility (AMS) in sedimentary rocks results from depositional, diagenetic, syn- and post-sedimentary processes that affect magnetic grains. Some studies have also shown the potential role played by post-depositional fluid flow in detrital and carbonate formations. Here we present a new case study of Middle-Upper Jurassic sandstones where secondary iron oxides, precipitated from fluids that migrated through pores, give rise to the AMS. These sandstones are well exposed in the Un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…We suggest that the axes interspersion in a plane perpendicular to the cleavage reveals the preservation of the lozenge‐shape petrofabric formed by crosscutting normal shear faults/fractures during the initial brittle stage of deformation, when the marly sediments were not completely lithified (Remitti et al., 2007; Vannucchi et al., 2010); P5 represents a local variation observed close to the contact with the Fiumalbo shale (T1‐B4) and without any relationship with the structural data. Possible explanations are: (a) higher contribution of ferromagnetic minerals and the presence of a mixed/intermediate magnetic fabric (Ferré, 2002; Pueyo Anchuela et al., 2010), considering that this pattern shows the highest χ m values; (b) percolation of ferruginous fluids (Ejembi et al., 2020); and (c) preservation of a strong original fabric.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We suggest that the axes interspersion in a plane perpendicular to the cleavage reveals the preservation of the lozenge‐shape petrofabric formed by crosscutting normal shear faults/fractures during the initial brittle stage of deformation, when the marly sediments were not completely lithified (Remitti et al., 2007; Vannucchi et al., 2010); P5 represents a local variation observed close to the contact with the Fiumalbo shale (T1‐B4) and without any relationship with the structural data. Possible explanations are: (a) higher contribution of ferromagnetic minerals and the presence of a mixed/intermediate magnetic fabric (Ferré, 2002; Pueyo Anchuela et al., 2010), considering that this pattern shows the highest χ m values; (b) percolation of ferruginous fluids (Ejembi et al., 2020); and (c) preservation of a strong original fabric.…”
Section: Discussionmentioning
confidence: 99%
“…P5 represents a local variation observed close to the contact with the Fiumalbo shale (T1‐B4) and without any relationship with the structural data. Possible explanations are: (a) higher contribution of ferromagnetic minerals and the presence of a mixed/intermediate magnetic fabric (Ferré, 2002; Pueyo Anchuela et al., 2010), considering that this pattern shows the highest χ m values; (b) percolation of ferruginous fluids (Ejembi et al., 2020); and (c) preservation of a strong original fabric.…”
Section: Discussionmentioning
confidence: 99%
“…In the past few decades, many studies have demonstrated that anisotropy of magnetic susceptibility (AMS, also termed magnetic fabric), a comparatively rapid tool, has delivered crucial information on basin evolution (e.g., Mattei et al, 1997;Cifelli et al, 2005;Oliva-Urcia et al, 2010, 2011, 2013Yu et al, 2014;Tang et al, 2015;Li et al, 2020aLi et al, , 2020cLi et al, , 2021Jiang et al, 2022;Zhang et al, 2022a), emplacement of igneous bodies (e.g., Hrouda, 1982;Bascou et al, 2005;Antolín-Tomás et al, 2009;Cañón-Tapia and Mendoza-Borunda, 2014;Yan et al, 2019), fold/fault deformation (e.g., Aubourg et al, 1999;Saint-Bezar et al, 2002;Evans et al, 2003;Luo et al, 2009;García-Lasanta et al, 2015), and paleocurrent directions (e.g., Tarling and Hrouda, 1993;Pueyo Anchuela et al, 2013;Ejembi et al, 2020;Bilardello, 2021). A fundamental step prior to interpreting AMS data is to ascertain what minerals give rise to the magnetic fabric.…”
Section: Introductionmentioning
confidence: 99%